Pemberdayaan Komite Sekolah melalui Strategi Manajerial Kepala Sekolah - M. Zidan Nur; Fridiyanto Fridiyanto; Husarida Husarida (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to analyze the principal’s strategies in empowering the school committee at Madrasah Aliyah Laboratory Kota Jambi and their impact on educational program development and community support. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive analysis technique. The findings reveal that the principal’s strategy in empowering the school committee is implemented through three main stages: planning, organizing, and supervising. The active involvement of the school committee in program planning and implementation contributes to the establishment of intra-curricular and extracurricular activities, particularly religious programs, and enhances community participation and support for the school. This study concludes that participatory and collaborative leadership strategies play a crucial role in optimizing the function of the school committee as a strategic partner in improving educational quality.